A Study to Assess the Compliance to Medication among Type 2 Diabetic Patients at Selected Rural Community in Kanchipuram District, Tamil Nadu (Medico Legal Update, 2020)
The Diabetis is one of the most common chronic disorder across the world and the number of diabeticpatients is on the rise .Majority of patients with type 2 diabetics fail to control glycaemia with diet andexercises .Lack of adherence to diabetic medication causes glycemic control and causes and can lead totreatment failure, development of complications and increases mortality.The objectives of the study were to assess the compliance to medications among type 2 diabetic patient andthe demographic variables. A non-probability- purposive sampling technique is used to collect data from thesamples. The sample size was 60 samples at selected rural community.The research design used in this study is Non experimental, Descriptive Research Design where MoriskyMedication Adherence Scales is to determine the level of compliance of medication . The level was assessedby questionnaires. The result shows 1(2%) of sample had low adherence, 12(20%) of the sample had mediumadherence, 47(78%) of sample had high adherence. There was significant association between the age, nosignificant association between other demographic variables.